Calciphylaxis in chronic, non-dialysis-dependent renal disease - Pliquett, Rainer U (BioMed Central, 2003)
BACKGROUND: Calciphylaxis cutis is characterized by media calcification of arteries and, most prominently, of cutaneous and subcutaneous arterioles occurring in renal insufficiency patients. CASE REPORT: A 53-year-old woman with chronic cardiac and renal failure complained of painful crural, non-varicosis ulcers. She was hospitalized in an immobilized condition due to both the crural ulcerations and the existing heart-failure state (NYHA III-IV) having pleural and pericardial effusions, atrial fibrillation and weight loss of 30 kg over the past year. Despite normalization of calcium-phosphorus balance and improvement of renal function, the clinical course of crural ulcerations deteriorated during the following 3 months. After failure of surgical debridements, multiple courses of sterile-maggot therapy were introduced at a late stage to stabilize the wounds. The patient died of recurrent wound infections and sepsis paralleled by exacerbations of renal malfunction. CONCLUSIONS: The role of renal disease in vascular complications is discussed. Sterile-maggot debridement may constitute a therapy for the ulcerated calciphylaxis at an earlier stage, i.e. when first ulcerations appear.